Performance Management Approach for Digital Platforms in B2B Markets - Özcan, Leon; Kirchberg, Lisa; Koldewey, Christian; Dumitrescu, Roman (The Role of Innovation: Past, Present, Future)
Digital platforms have already led to disruptions in multiple B2C markets and are becoming increasingly dominant in B2B markets. As a result, more and more companies are trying to participate in the platform economy. However, the successful development and operation of a digital platform is associated with significant challenges, which leads to 85% of all platforms failing. A core challenge is the dynamic nature of the platform economy, with varying strategic objectives at different stages in the platform lifecycle. Platform operators must continuously monitor platform progress and adjust their strategy. Utilizing action research in the real-world platform project AI Marketplace, we developed a lifecycle-oriented performance management approach for digital platforms in B2B markets. It enables platform operators to reflect on their position in the platform lifecycle, derive relevant strategic objectives, and monitor them with suitable key performance indicators. Hence, allowing them to secure the long-term success of their platform business.
Keywords: Digital Platform; Two-Sided Market; Multi-Sided Market; Platform Lifecycle; Platform Monitoring; Performance Management

Hyphenation of ultra-high-performance liquid chromatography and ion mobility mass spectrometry for the analysis of sequence-defined oligomers with different functionalities and tacticity - Berg, Marie-Theres; Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
In recent years, sequence-defined oligomers (SDOs) gained increasing interest due to their perfectly controlled molecular structure, thus providing defined properties. In order to tune the properties, different functionalities need to be incorporated into the oligomers and the chain tacticity needs to be controlled. Beside the synthesis of SDOs, suitable methods need to be found to analyze the molecular structure. In this work, oligomers exhibiting an alternating or block-wise sequence of side chain functionalities were analyzed using a hyphenation of ultra-high-performance liquid chromatography and electrospray ionization mass spectrometry enhanced by ion mobility separation (IMS). Moieties in the side chains were varied according to polarity and bulkiness. Moreover, chain tacticity was varied. Drift times in the IMS cell and the corresponding collision cross section (CCS) values were shown to be individual parameters allowing the identification of SDOs, even in the case that SDO structures only differ in sequence or tacticity of side chain functionalities. Thus, a library of CCS values was obtained as reference used for the analysis of complex mixtures of SDOs.
Keywords: Ultra-high-performance liquid chromatography; ion mobility separation; mass spectrometry; LC-MS hyphenation; sequence-defined oligomers

Die Wirksamkeit von Lernzielen für Studienleistungen – eine experimentelle Studie - Auer, Thorsten Fabian (die hochschullehre)
According to the German Rectors’ Conference (HRK), German higher education teaching fails to meet the demand to integrate competence-oriented learning objectives. Despite a wide-ranging debate on the use of learning objectives, empirical research on their effectiveness is scarce. The present study uses the features of digital teaching platforms to investigate the perception and effectiveness of learning objectives applying a randomised controlled experiment followed by a survey in a course for undergraduate economics students (N = 30). Controlling group preconditions and the treatment effect allows to draw conclusions about the different learning outcomes of the student groups. The specification of behaviour-oriented learning objectives in the online course system leads to significantly better performance in the treatment group. A stronger perception of the learning objectives in the treatment group supports this effect that remains significant in a regression analysis. Thus, the study provides an empirical justification to integrate learning objectives in university teaching.
Keywords: learning objectives; academic performance; perception; teaching methods; experiment

BBE: Basin-Based Evaluation of Multimodal Multi-objective Optimization Problems - Heins, Jonathan; Rook, Jeroen; Schäpermeier, Lennart; Kerschke, Pascal; Bossek, Jakob; Trautmann, Heike (Parallel Problem Solving from Nature (PPSN XVII))
In multimodal multi-objective optimization (MMMOO), the focus is not solely on convergence in objective space, but rather also on explicitly ensuring diversity in decision space. We illustrate why commonly used diversity measures are not entirely appropriate for this task and propose a sophisticated basin-based evaluation (BBE) method. Also, BBE variants are developed, capturing the anytime behavior of algorithms. The set of BBE measures is tested by means of an algorithm configuration study. We show that these new measures also transfer properties of the well-established hypervolume (HV) indicator to the domain of MMMOO, thus also accounting for objective space convergence. Moreover, we advance MMMOO research by providing insights into the multimodal performance of the considered algorithms. Specifically, algorithms exploiting local structures are shown to outperform classical evolutionary multi-objective optimizers regarding the BBE variants and respective trade-off with HV.
Keywords: Anytime behavior; Benchmarking; Continuous optimization; Multi-objective optimization; Multimodality; Performance metric

Module-Inverters (Microinverters): Influence of Module Size on Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EU PVSEC 2021))
Efficiencies and energy yields of microinverters available on the market during 2014‒2021 have been measured, compared, and ranked. Conversion efficiencies as a function of load have been measured indoors with high accuracy and ranked according to Euro- and CEC weightings. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules of 215 Wp (until 2020) and 360 Wp (starting 2021). Inverters with two inputs have been fed by two of those modules. DC input, AC power output and energy yield of each microinverter have been recorded by individual calibrated electricity meters. CEC and EU efficiency rankings have been computed and compared. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation y = ax + b resulting in the actual yield, any module & inverter configuration can be characterized by just the coefficients a and b.
Keywords: AC-modules; Microinverter; Power Conditioning; Efficiency; Yield; PV module size; saturation; performance

Elevated Temperatures Affecting Efficiency, Overall Performance and Energy Yield of PV Microinverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EU PVSEC 2020)
During comparative measurements of different PV microinverters, two yield issues came up that could not be explored via conventional efficiency measurements, but do have a significant impact on electrical energy yield: First category of issues are either sluggish or nervously acting maximum–power–point–tracking devices, which lead to reduced energy yields. The other category of issues is thermal: As a first explanation for observed reduced energy yields, it has been assumed that the conversion efficiency degrades at higher operating temperatures. This matter has been investigated in this article: A change in conversion efficiency could not be observed for elevated operation temperatures up to 50°C, despite high-precision and repeated measurements. But it was found that some inverters temporarily interrupted (or entirely stopped) operation after long periods of running at high temperatures. Also, a reduction in potential maximum power output has been detected for those inverters. Summarizing: With a high degree of certainty it can be stated that those reported yield losses have been caused by the temporary shutdowns and power limitations of the inverters.
Keywords: AC-modules; Microinverter; Power Conditioning; Thermal Performance; Ventilation; Stability; Efficiency; Yield

A multi-objective perspective on performance assessment and automated selection of single-objective optimization algorithms - Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Applied Soft Computing)
We build upon a recently proposed multi-objective view onto performance measurement of single-objective stochastic solvers. The trade-off between the fraction of failed runs and the mean runtime of successful runs – both to be minimized – is directly analyzed based on a study on algorithm selection of inexact state-of-the-art solvers for the famous Traveling Salesperson Problem (TSP). Moreover, we adopt the hypervolume indicator (HV) commonly used in multi-objective optimization for simultaneously assessing both conflicting objectives and investigate relations to commonly used performance indicators, both theoretically and empirically. Next to Penalized Average Runtime (PAR) and Penalized Quantile Runtime (PQR), the HV measure is used as a core concept within the construction of per-instance algorithm selection models offering interesting insights into complementary behavior of inexact TSP solvers.
Keywords: Algorithm selection; Multi-objective optimization; Performance measurement; Combinatorial optimization; Traveling Salesperson Problem

A Multi-Objective Perspective on Performance Assessment and Automated Selection of Single-Objective Optimization Algorithms - Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Applied Soft Computing)
We build upon a recently proposed multi-objective view onto performance measurement of single-objective stochastic solvers. The trade-off between the fraction of failed runs and the mean runtime of successful runs – both to be minimized – is directly analyzed based on a study on algorithm selection of inexact state-of-the-art solvers for the famous Traveling Salesperson Problem (TSP). Moreover, we adopt the hypervolume indicator (HV) commonly used in multi-objective optimization for simultaneously assessing both conflicting objectives and investigate relations to commonly used performance indicators, both theoretically and empirically. Next to Penalized Average Runtime (PAR) and Penalized Quantile Runtime (PQR), the HV measure is used as a core concept within the construction of per-instance algorithm selection models offering interesting insights into complementary behavior of inexact TSP solvers. \textbullet The multi-objective perspective is naturally generalizable to multiple objectives. \textbullet Proof of relationship between HV and the PAR in the considered bi-objective space. \textbullet New insights into complementary behavior of stochastic optimization algorithms.
Keywords: Algorithm selection; Combinatorial optimization; Multi-objective optimization; Performance measurement; Traveling Salesperson Problem

Paying for Performance in Private Equity: Evidence from Venture Capital Partnerships - Hüther, Niklas; Robinson, David T.; Sievers, Sönke; Hartmann-Wendels, Thomas (Management Science (VHB-JOURQUAL 3 Ranking A+))
We offer the first empirical analysis connecting the timing of general partner (GP) compensation to private equity fund performance. Using detailed information on limited partnership agreements between private equity limited and general partners, we find that “GP-friendly” contracts—agreements that pay general partners on a deal-by-deal basis instead of withholding carried interest until a benchmark return has been earned—are associated with higher returns, both gross and net of fees. This is robust to measures of performance persistence, time period effects, and other contract terms and is related to exit-timing incentives. Timing practices balance GP incentives against limited partner downside protection.
Keywords: venture capital; compensation; private equity; VC partnership; pay-performance relation

Using High Performance Computing for Unrelated Parallel Machine Scheduling with Sequence-Dependent Setup Times: Development and Computational Evaluation of a Parallel Branch-and-Price Algorithm - Rauchecker, Gerhard; Schryen, Guido (Computers & Operations Research)
Scheduling problems are essential for decision making in many academic disciplines, including operations management, computer science, and information systems. Since many scheduling problems are NP-hard in the strong sense, there is only limited research on exact algorithms and how their efficiency scales when implemented on parallel computing architectures. We address this gap by (1) adapting an exact branch-and-price algorithm to a parallel machine scheduling problem on unrelated machines with sequence- and machine-dependent setup times, (2) parallelizing the adapted algorithm by implementing a distributed-memory parallelization with a master/worker approach, and (3) conducting extensive computational experiments using up to 960 MPI processes on a modern high performance computing cluster. With our experiments, we show that the efficiency of our parallelization approach can lead to superlinear speedup but can vary substantially between instances. We further show that the wall time of serial execution can be substantially reduced through our parallelization, in some cases from 94 hours to less than six minutes when our algorithm is executed on 960 processes.
Keywords: parallel machine scheduling with setup times; parallel branch-and-price algorithm; high performance computing; master/worker parallelization

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

Multi-Objective Performance Measurement: Alternatives to PAR10 and Expected Running Time - Bossek, Jakob; Trautmann, Heike (Learning and Intelligent Optimization)
A multiobjective perspective onto common performance measures such as the PAR10 score or the expected runtime of single-objective stochastic solvers is presented by directly investigating the tradeoff between the fraction of failed runs and the average runtime. Multi-objective indicators operating in the bi-objective space allow for an overall performance comparison on a set of instances paving the way for instance-based automated algorithm selection techniques.
Keywords: Algorithm selection; Performance measurement

Performance Assessment of Multi-Objective Evolutionary Algorithms with the R Package ecr - Bossek, Jakob (Proceedings of the Genetic and Evolutionary Computation Conference Companion)
Assessing the performance of stochastic optimization algorithms in the field of multi-objective optimization is of utmost importance. Besides the visual comparison of the obtained approximation sets, more sophisticated methods have been proposed in the last decade, e. g., a variety of quantitative performance indicators or statistical tests. In this paper, we present tools implemented in the R package ecr, which assist in performing comprehensive and sound comparison and evaluation of multi-objective evolutionary algorithms following recommendations from the literature.
Keywords: evolutionary optimization; performance assessment; software-tools

Parameterization of State-of-the-Art Performance Indicators: A Robustness Study Based on Inexact TSP Solvers - Kerschke, Pascal; Bossek, Jakob; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference Companion)
Performance comparisons of optimization algorithms are heavily influenced by the underlying indicator(s). In this paper we investigate commonly used performance indicators for single-objective stochastic solvers, such as the Penalized Average Runtime (e.g., PAR10) or the Expected Running Time (ERT), based on exemplary benchmark performances of state-of-the-art inexact TSP solvers. Thereby, we introduce a methodology for analyzing the effects of (usually heuristically set) indicator parametrizations - such as the penalty factor and the method used for aggregating across multiple runs - w.r.t. the robustness of the considered optimization algorithms.
Keywords: algorithm selection; optimization; performance measures; transportation; travelling salesperson problem

Leveraging TSP Solver Complementarity through Machine Learning - Kerschke, Pascal; Kotthoff, Lars; Bossek, Jakob; Hoos, Holger H.; Trautmann, Heike (Evolutionary Computation)
The Travelling Salesperson Problem (TSP) is one of the best-studied NP-hard problems. Over the years, many different solution approaches and solvers have been developed. For the first time, we directly compare five state-of-the-art inexact solvers— namely, LKH, EAX, restart variants of those, and MAOS— on a large set of well-known benchmark instances and demonstrate complementary performance, in that different instances may be solved most effectively by different algorithms. We leverage this complementarity to build an algorithm selector, which selects the best TSP solver on a per-instance basis and thus achieves significantly improved performance compared to the single best solver, representing an advance in the state of the art in solving the Euclidean TSP. Our in-depth analysis of the selectors provides insight into what drives this performance improvement.
Keywords: automated algorithm selection; machine learning.; performance modeling; Travelling Salesperson Problem

Paying for Performance in Private Equity: Evidence from VC Partnerships - Hüther, Niklas; Robinson, David; Sievers, Sönke; Hartmann-Wendels, Thomas (SSRN Electronic Journal)
We offer the first empirical analysis connecting the timing of general partner (GP) compensation to private equity fund performance. Using detailed information on limited partnership agreements between private equity limited and general partners, we find that "GP-friendly" contracts - agreements that pay general partners on a deal-by-deal basis instead of withholding carried interest until a benchmark return has been earned - are associated with higher returns, both gross and net of fees. This is robust to measures of performance persistence, time period effects, and other contract terms, and is related to exit-timing incentives. Timing practices balance GP incentives against limited partner downside protection.
Keywords: venture capital; compensation; private equity; VC partnership; pay-performance relation

Computational self-awareness as design approach for visual sensor nodes - Guettatfi, Zakarya; Hübner, Philipp; Platzner, Marco; Rinner, Bernhard (12th International Symposium on Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC))
Keywords: embedded systems; image sensors; power aware computing; wireless sensor networks; Zynq-based VSN node prototype; computational self-awareness; design approach; platform levels; power consumption; visual sensor networks; visual sensor nodes; Cameras; Hardware; Middleware; Multicore processing; Operating systems; Runtime; Reconfigurable platforms; distributed embedded systems; performance-resource trade-off; self-awareness; visual sensor nodes

High-Performance Computing for Scheduling Decision Support: A Parallel Depth-First Search Heuristic - Rauchecker, Gerhard; Schryen, Guido (Australasian Conference on Information Systems)
Many academic disciplines - including information systems, computer science, and operations management - face scheduling problems as important decision making tasks. Since many scheduling problems are NP-hard in the strong sense, there is a need for developing solution heuristics. For scheduling problems with setup times on unrelated parallel machines, there is limited research on solution methods and to the best of our knowledge, parallel computer architectures have not yet been taken advantage of. We address this gap by proposing and implementing a new solution heuristic and by testing different parallelization strategies. In our computational experiments, we show that our heuristic calculates near-optimal solutions even for large instances and that computing time can be reduced substantially by our parallelization approach.
Keywords: scheduling; decision support; heuristic; high performance computing; parallel algorithms

Advancing Research on Loyalty Programs: A Future Research Agenda. - Breugelmans, Els; Bijmolt, Tammo H A; Zhang, Jie; Basso, Leonardo J; Dorotic, Matilda; Kopalle, Praveen; Minnema, Alec; Mijnlieff, Willem Jan; Wünderlich, Nancy (Marketing Letters)
Despite the growing literature on loyalty program (LP) research, many questions remain underexplored. Driven by advancements in information technology, marketing analytics, and consumer interface platforms (e.g., mobile devices), there have been many recent developments in LP practices around the world. They impose new challenges and create exciting opportunities for future LP research. The main objective of this paper is to identify missing links in the literature and to craft a future research agenda to advance LP research and practice. Our discussion focuses on three key areas: (1) LP designs, (2) Assessment of LP performance, and (3) Emerging trends and the impact of new technologies. We highlight several gaps in the literature and outline research opportunities in each area.
Keywords: Loyalty programs; Loyalty program design; Loyalty program performance assessment; Emerging trends; Partnership loyalty programs; Customer relationship management

A hardware/software infrastructure for performance monitoring on LEON3 multicore platforms - Ho, Nam; Kaufmann, Paul; Platzner, Marco (24th Intl. Conf. on Field Programmable Logic and Applications (FPL))
Keywords: Linux; hardware-software codesign; multiprocessing systems; parallel processing; LEON3 multicore platform; Linux kernel; PMU; hardware counters; hardware-software infrastructure; high performance embedded computing; perf_event; performance monitoring unit; Computer architecture; Hardware; Monitoring; Phasor measurement units; Radiation detectors; Registers; Software

Towards self-adaptive caches: A run-time reconfigurable multi-core infrastructure - Ho, Nam; Kaufmann, Paul; Platzner, Marco (2014 IEEE Intl. Conf. on Evolvable Systems (ICES))
Keywords: Linux; cache storage; embedded systems; granular computing; multiprocessing systems; reconfigurable architectures; Leon3 SPARe processor; custom logic events; evolvable-self-adaptable processor cache; fine granular profiling; integer unit events; measurement infrastructure; microarchitectural events; multicore embedded system; perf_event standard Linux performance measurement interface; processor properties; run-time reconfigurable memory-to-cache address mapping engine; run-time reconfigurable multicore infrastructure; split-level caching; Field programmable gate arrays; Frequency locked loops; Irrigation; Phasor measurement units; Registers; Weaving

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part I: Ideal Excitation. - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Piezoelectric inertia motors, also known as ``stick--slip drives'', use the inertia of a body to drive it in small steps by means of a friction contact. While these steps are classically assumed to involve stiction and sliding, the motors can also operate in ``slip--slip'' mode without any phase of static friction. This contribution provides a systematic investigation and performance comparison of different stick--slip and slip--slip modes of operation. Different criteria for comparing the motional performance of inertia motors are defined: Steady state velocity, smoothness of motion, and start-up time. Using the example of a translational inertia motor excited by an ideal displacement signal, it is found that the maximum velocity reachable in stick--slip operation is limited principally, while continuous slip--slip operation allows very high velocities. For the investigated driving signals, the motor velocity is proportional to the square root of the actuator stroke. The motor performance with these ideal signals defines an upper boundary for the performance of real motors.
Keywords: Inertia motor; Stick--slip drive; Mode of operation; Performance indicator; Velocity maximization; Actuator stroke

Model-driven Performance Engineering of Self-adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen ({Proceedings of the 8th International ACM SIGSOFT Conference on Quality of Software Architectures (QoSA)})
Keywords: model-driven performance engineering; self-*; Self-adaptation; software performance

Perils of Managing the Service Profit Chain: The Role of Time Lags and Feedback Loops. - Evanschitzky, Heiner; Wangenheim, Florian v; Wünderlich, Nancy (Journal of Retailing)
The tendency of managers to focus on short-term results rather than on sustained company success is of particular importance to retail marketing managers, because marketing activities involve expenditures which may only pay off in the longer term. To address the issue of myopic management, our study shows how the complexity of the service profit chain (SPC) can cause managers to make suboptimal decisions. Hence, our paper departs from past research by recognizing that understanding the temporal interplay between operational investments, employee satisfaction, customer satisfaction, and operating profit is essential to achieving sustained success. In particular, we intend to improve understanding of the functioning of the SPC with respect to time lags and feedback loops. Results of our large-scale longitudinal study set in a multi-outlet retail chain reveal time-lag effects between operational investments and employee satisfaction, as well as between customer satisfaction and performance. These findings, along with evidence of a negative interaction effect of employee satisfaction on the relationship between current performance and future investments, show the substantial risk of mismanaging the SPC. We identify specific situations in which the dynamic approach leads to superior marketing investment decisions, when compared to the conventional static view of the SCP. These insights provide valuable managerial guidance for effectively managing the SPC over time.
Keywords: Employee satisfaction; Customer satisfaction; Performance; Service profit chain; Feedback loops; Time lags; Myopic marketing management

To buy or not to buy? The value of contradictory analyst signals - Kanne, Stefan; Klobucnik, Jan; Kreutzmann, Daniel; Sievers, Sönke (Financial Markets and Portfolio Management (VHB-JOURQUAL 3 Ranking C))
We study the predictive ability of individual analyst target price changes for post-event abnormal stock returns within each recommendation category. Although prior studies generally demonstrate the investment value of target prices, we find that target price changes do not cause abnormal returns within each recommendation level. Instead, contradictory analyst signals (e.g., strong buy reiterations with large target price decreases) neutralize each other, whereas confirmatory signals reinforce each other. Further, our analysis reveals that large target price downgrades can be explained by preceding stock price decreases. However, upgrades are not preceded by stock price increases, thereby demonstrating asymmetric analyst behavior when adjusting target prices to stock prices. Our results suggest that investors should treat recommendations with caution when they are issued with large contradictory target price changes. Thus, instead of blindly following a recommendation, investors might put more weight on the change in the corresponding target price and consider transaction costs.
Keywords: Analyst recommendation; Target price; Stock performance; Trading strategy

On the Properties of the R2 Indicator - Brockhoff, Dimo; Wagner, Tobias; Trautmann, Heike (Proceedings of the 14th Annual Conference on Genetic and Evolutionary Computation)
In multiobjective optimization, set-based performance indicators are commonly used to assess the quality of a Pareto front approximation. Based on the scalarization obtained by these indicators, a performance comparison of multiobjective optimization algorithms becomes possible. The R2 and the Hypervolume (HV) indicator represent two recommended approaches which have shown a correlated behavior in recent empirical studies. Whereas the HV indicator has been comprehensively analyzed in the last years, almost no studies on the R2 indicator exist. In this paper, we thus perform a comprehensive investigation of the properties of the R2 indicator in a theoretical and empirical way. The influence of the number and distribution of the weight vectors on the optimal distribution of μ solutions is analyzed. Based on a comparative analysis, specific characteristics and differences of the R2 and HV indicator are presented.
Keywords: hypervolume indicator; multiobjective optimization; performance assessment; r2 indicator

Prior entry explains order reversals in the attentional blink. - Olivers, Christian N. L.; Hilkenmeier, Frederic; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
When two targets are presented in rapid succession, the first target (T1) is usually identified, but the second target (T2) is often missed. A remarkable exception to this 'attentional blink' occurs when T2 immediately follows the first T1, at lag 1. It is then often spared but reported in the wrong order—that is, before T1. These order reversals have led to the hypothesis that 'lag 1 sparing' occurs because the two targets merge into a single episodic representation. Here, we report evidence consistent with an alternative theory: T2 receives more attention than T1, leading to prior entry into working memory. Two experiments showed that the more T2 performance exceeded that for T1, the more order reversals were made. Furthermore, precuing T1 led to a shift in performance benefits from T2 to T1 and to an equivalent reduction in order reversals. We conclude that it is not necessary to assume episodic integration to explain lag 1 sparing or the accompanying order reversals. (PsycINFO Dat
Keywords: attentional blink; order reversals; prior entry; working memory; visual attention; attentional performance; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Discrimination (Psychology); Female; Humans; Male; Memory; Short-Term; Pattern Recognition; Visual; Psychophysics; Reaction Time; Reversal Learning; Sensory Gating; Serial Learning; Young Adult; Eyeblink Reflex; Stimulus Change; Stimulus Parameters; Visual Attention; Attentional Blink; Short Term Memory

Performance Estimation Framework for Automated Exploration of CPU-Accelerator Architectures - Kenter, Tobias; Platzner, Marco; Plessl, Christian; Kauschke, Michael (Proc. Int. Symp. on Field-Programmable Gate Arrays (FPGA))
Keywords: design space exploration; LLVM; partitioning; performance; estimation; funding-intel

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Assertion-Based Verification of RTOS Properties - Oliveira, Marcio F. S.; Zabel, Henning; Müller, Wolfgang (Proceedings of DATE’10)
Today, mobile and embedded real time systems have to cope with the migration and allocation of multiple software tasks running on top of a real time operating system (RTOS) residing on one or several processors. For scaling of each task set and processor configuration, instruction set simulation and worst case timing analysis are typically applied. This paper presents a complementary approach for the verification of RTOS properties based on an abstract RTOS-Model in SystemC. We apply IEEE P1850 PSL for which we present an approach and first experiences for the assertion-based verification of RTOS properties.
Keywords: Operating systems; Real time systems; Timing; Hardware; Analytical models; Embedded software; Software systems; Processor scheduling; Software performance; Performance analysis

Increased Accuracy through Noise Injection in Abstract RTOS Simulation - Zabel, Henning; Müller, Wolfgang (Proceedings of DATE'09)
Today, mobile and embedded real-time systems have to cope with the migration and allocation of multiple software tasks running on top of a real-time operating system (RTOS) residing on one or multiple system processors. Abstract RTOS simulations and timing analysis applies for fast and early estimation to configure it towards the individual needs of the application and environment. In this context, a high accuracy of the simulation compared to an instruction set simulation (ISS) is of key importance. In this paper, we investigate the accuracy of abstract RTOS simulation and compare it to ISS and the behavior of the physical system. We show that we can reach an increased accuracy of the simulation when we inject noise into the time model. Our results indicate that it is sufficient to inject uniformly distributed random time values to the RTOS real-time clock.
Keywords: Timing; Analytical models; Clocks; Performance analysis; Scheduling; Operating systems; Delay; Real time systems; Application software; Context modeling

IMORC: Application Mapping, Monitoring and Optimization for High-Performance Reconfigurable Computing - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Proc. Int. Symp. on Field-Programmable Custom Computing Machines (FCCM))
Mapping applications that consist of a collection of cores to FPGA accelerators and optimizing their performance is a challenging task in high performance reconfigurable computing. We present IMORC, an architectural template and highly versatile on-chip interconnect. IMORC links provide asynchronous FIFOs and bitwidth conversion which allows for flexibly composing accelerators from cores running at full speed within their own clock domains, thus facilitating the re-use of cores and portability. Further, IMORC inserts performance counters for monitoring runtime data. In this paper, we first introduce the IMORC architectural template and the on-chip interconnect, and then demonstrate IMORC on the example of accelerating the k-th nearest neighbor thinning problem on an XD1000 reconfigurable computing system. Using IMORC's monitoring infrastructure, we gain insights into the data-dependent behavior of the application which, in turn, allow for optimizing the accelerator.
Keywords: IMORC; interconnect; performance

A Comparison of Soft-Feature Distributed Speech Recognition with Candidate Codecs for Speech Enabled Mobile Services - Ion, Valentin; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2005))
In this paper we present a comparison of the recently proposed Soft-Feature Distributed Speech Recognition (SFDSR) with the two evaluated candidate codecs for Speech Enabled Services over wireless networks: Adaptive Multirate Codec (AMR) and the ETSI Extended Advanced Front-End for Distributed Speech Recognition (XAFE). It is shown that SFDSR achieves the best recognition performance on a simulated GSM transmission, followed by XAFE and AMR.We also present some new results concerning SFDSR which demonstrate the versatility of the approach. Further, a simple method is introduced which considerably reduces the computational effort.
Keywords: adaptive codes; adaptive multirate codec; AMR; distributed speech recognition; ETSI; extended advanced front-end; recognition performance; SFDSR; simulated GSM transmission; soft-feature distributed speech recognition; speech codecs; speech coding; speech recognition; variable rate codes; XAFE

Evidence against response bias in temporal order tasks with attention manipulation by masked primes. - Scharlau, Ingrid (Psychological Research)
Attending to a location shortens the perceptual latency of stimuli appearing at this location (perceptual latency priming). According to attentional explanations, perceptual latency priming relies on the speeded transfer of attended visual information into an internal model. However, doubts about the attentional origin have repeatedly been raised because efforts to minimize response bias have been insufficient in most studies. Five experiments investigated the contribution of a response bias to perceptual latency priming (judgment bias due to the two-alternative forced-choice method and due to the existence of the prime, criterion effects or second-order bias, sensorimotor priming). If any, only small response biases were found. The results thus support the attentional explanation. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: response bias; temporal order tasks; attention manipulation; masked primes; perceptual latency priming; Adult; Attention; Discrimination Learning; Female; Humans; Male; Memory; Short-Term; Orientation; Pattern Recognition; Visual; Perceptual Masking; Psychomotor Performance; Psychophysics; Reaction Time; Serial Learning; Attention; Latent Learning; Priming; Response Bias; Visual Perception; Response Latency; Temporal Order (Judgment)

Scheduling in HPC Resource Management Systems: Queuing vs. Planning - Hovestadt, Matthias; Kao, Odej; Keller, Axel; Streit, Achim (Proc. Workshop on Job Scheduling Strategies for Parallel Processing (JSSPP))
Nearly all existing HPC systems are operated by resource management systems based on the queuing approach. With the increasing acceptance of grid middleware like Globus, new requirements for the underlying local resource management systems arise. Features like advanced reservation or quality of service are needed to implement high level functions like co-allocation. However it is difficult to realize these features with a resource management system based on the queuing concept since it considers only the present resource usage. In this paper we present an approach which closes this gap. By assigning start times to each resource request, a complete schedule is planned. Advanced reservations are now easily possible. Based on this planning approach functions like diffuse requests, automatic duration extension, or service level agreements are described. We think they are useful to increase the usability, acceptance and performance of HPC machines. In the second part of this paper we present a planning based resource management system which already covers some of the mentioned features.
Keywords: High Performance Computing; Service Level Agreement; Grid Resource; Resource Management System; Advance Reservation

TKDM – A Reconfigurable Co-processor in a PC's Memory Slot - Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Field Programmable Technology (ICFPT))
This paper presents TKDM, a PC-based high-performance reconfigurable computing environment. The TKDM hardware consists of an FPGA module that uses the DIMM (dual inline memory module) bus for high-bandwidth and low-latency communication with the host CPU. The system's firmware is integrated with the Linux host operating system and offers functions for data communication and FPGA reconfiguration. The intended use of TKDM is that of a dynamically reconfigurable co-processor for data streaming applications. The system's firmware can be customized for specific application domains to facilitate simple and easy-to-use programming interfaces.
Keywords: coprocessor; DIMM; memory bus; FPGA; high performance computing

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)